2009
DOI: 10.1188/09.onf.e39-e46
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Behaviors of Nursing and Midwifery Students Regarding Breast Self-Examination in Turkey

Abstract: The findings suggest that nursing and midwifery students should be thoroughly prepared to perform BSE on themselves so they can educate other women about this important preventive procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 18 publications
2
24
1
1
Order By: Relevance
“…In the studies conducted by Sambanje and Mafuvadze (2012) and Al-Sharbatti et al (2013) unlike the medical and non-medical university students studying in sections in all of the knowledge and awareness of breast cancer has been reported to be low. It has reported that the nursing and midwifery students had sufficient information about BSE from varied sources (Memis et al, 2009;Bien et al, 2014). This recent study of the findings of studies conducted in Turkey and in the world of health care workers in the future will be unlike breast cancer awareness among female students show that it is pleasing to a good level.…”
Section: Discussionmentioning
confidence: 87%
“…In the studies conducted by Sambanje and Mafuvadze (2012) and Al-Sharbatti et al (2013) unlike the medical and non-medical university students studying in sections in all of the knowledge and awareness of breast cancer has been reported to be low. It has reported that the nursing and midwifery students had sufficient information about BSE from varied sources (Memis et al, 2009;Bien et al, 2014). This recent study of the findings of studies conducted in Turkey and in the world of health care workers in the future will be unlike breast cancer awareness among female students show that it is pleasing to a good level.…”
Section: Discussionmentioning
confidence: 87%
“…It is in this way that they can play an effective role in resolving these issues [6][7][8]. It has been pointed out in one study that although it is part of the job of nurses to provide education in matters of SH/RH, nurses in fact are lacking the knowledge to do this [9].…”
Section: Literature Reviewmentioning
confidence: 94%
“…Education of nursing and midwifery provide a positive effect on knowledge, attitude, and behavior towards BSE. 34 In addition, there were differences in health belief about BSE and its practice between nursing and their mothers. 35 While other studies show that the female university students have mild knowledge of breast cancer symptoms and management.…”
mentioning
confidence: 99%